KAJIAN PENGEMBANGAN KAPASITAS ANGGOTA DPRD KABUPATEN PELALAWAN - Ahmad Hidir (Menara Ilmu, 2017)
The study of Capacity development of Pelalawan District DPRD Members aimed to find out what factors need to be developed and anticipated for the need of human resource development and the capacity develpment model of DPRD members and to find the model of policies and programs to improve the human resources and DPRD Institution in accordance with the demand and development of the community in Pelalawan Regency . The result of the study on Capacity development of Pelalawan District DPRD members is generally good enough, but there are still some obstacles both internally and externally analyzed by using SWOT analysis. To minimize such obstacles, some action plans were required to be carried out, such as added Administrative pesonil in accordance with the needs of the Ministry, Education and Training in accordance with the needs of members of the Board to perform 3 functions of the Board. Expert Staff and technical team were capable of supporting the duties of Device according to their fields and expertise and work visit and comparative study which is more meaningful, transparent and accountable.Keywords: Capacity development, DPRD